2016
DOI: 10.3390/socsci5040068
|View full text |Cite
|
Sign up to set email alerts
|

Angry and Alone: Demographic Characteristics of Those Who Post to Online Comment Sections

Abstract: Abstract:The Internet and social media afford individuals the opportunity to post their thoughts instantaneously and largely without filters. While this has tremendous democratic potential, it also raises questions about the quality of the discourse these technological changes portend. Online comment sections may be a particularly unique form of communication within social media to investigate because of their ubiquitous and often anonymous nature. A longitudinal examination of Pew Center data over the course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Even if there are other underlying factors involved in why social media has become such a dominant platform for news media's comments sections, comments made by interviewees in this study show that the lack of user anonymity has been a central factor. This claim is supported by research (Hille and Bakker, 2014;Artime, 2016).…”
Section: Norms Values and Emotionsmentioning
confidence: 67%
See 2 more Smart Citations
“…Even if there are other underlying factors involved in why social media has become such a dominant platform for news media's comments sections, comments made by interviewees in this study show that the lack of user anonymity has been a central factor. This claim is supported by research (Hille and Bakker, 2014;Artime, 2016).…”
Section: Norms Values and Emotionsmentioning
confidence: 67%
“…Many of the channels responsible for our news diet have, in recent years, relocated much of their reader interactivity from their own websites to social media (Santana, 2014;Artime, 2016;Hong, 2012; Pew Research Center for the people and the press, 2010, 2016; Robinson, 2014;Weber, 2014), which has contributed to changing the ways in which news sources interact with readers (Hermida, 2010;Lee, 2015;Lee et al, 2017). A typical approach was to start with a simple presence on Facebook, where they linked to articles or made other updates.…”
Section: Negotiating the Benefits Of Maintaining Digital Platforms For User Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newspaper editors view comments as one of the most successful forms of audience interaction [18], and the intention is to continue supporting comment sections on online publications [19]. According to the Pew Research Center [20] about one in four Americans have contributed to comment sections. As many as 84% of newsreaders read comments, and studies have shown that reading comments can significantly affect readers' perception of public opinion, as well as change their personal opinion [21].…”
Section: Introductionmentioning
confidence: 99%
“…Newspaper comment sections have been described as a staple of the online experience (Finley, 2015). With approximately 90 percent of news sites having some form of comment section (Stroud, et al, 2017) it has become possible for readers of almost any newspaper to share their views to a large audience and add their voices to public debates (Artime, 2016). Newspaper comment sections provide an arena for public debate and have been found to shape the opinions of the readers and influence how journalists work (Toepfl and Piwoni, 2015).…”
Section: Introductionmentioning
confidence: 99%